Exchange rate forecasting on a napkin - Michele Ca' Zorzi; Michał Rubaszek (European Central Bank (ECB), 2018)
This paper shows that there are two regularities in foreign exchange markets in advanced countries with flexible regimes. First, real exchange rates are mean-reverting, as implied by the Purchasing Power Parity model. Second, the adjustment takes place via nominal exchange rates. These features of the data can be exploited, even on the back of a napkin, to generate nominal exchange rate forecasts that outperform the random walk. The secret is to avoid estimating the pace of mean reversion and assume that relative prices are unchanged. Direct forecasting or panel data techniques are better than the random walk but fail to beat this simple calibrated model.
Keywords: C32; F31; F37; F41; 330; exchange rates; forecasting; Purchasing Power Parity; panel data; mean reversion